Adverse childhood experiences, parenting, and socioeconomic status: Associations with internalizing and externalizing symptoms in adolescence. (March 2022) - Anderson, Allegra S.; Siciliano, Rachel E.; Henry, Lauren M.; Watson, Kelly H.; Gruhn, Meredith A.; Kuhn, Tarah M.; Ebert, Jon; Vreeland, Allison J.; Ciriegio, Abagail E.; Guthrie, Cara; Compas, Bruce E.
Abstract: Background: Adverse childhood experiences (ACEs), low socioeconomic status (SES), and harsh parenting practices each represent well-established risk factors for mental health problems. However, research supporting these links has often focused on only one of these predictors and psychopathology, and interactions among these variables in association with symptoms are not well understood. Objective: The current study utilized a cross-sectional, multi-informant, and multi-method design to investigate the associations of ACEs, SES, parenting, and concurrent internalizing and externalizing problems in adolescents. Participants and setting: Data are from a volunteer sample of 97 adolescents and their caregivers recruited from 2018 to 2021 in a southern U.S. metropolitan area to sample a range of exposure to ACEs. Methods: Multiple linear regression models were used to assess associations among adolescents' ACEs exposure, SES, observed parenting practices, and symptoms of internalizing and externalizing psychopathology. Results: Lower SES was associated with higher levels of internalizing and externalizing symptoms, while higher ACEs exposure and observed parenting were related to externalizing but not internalizing symptoms. Associations of adolescents' exposure to physical abuse and perceived financial insecurity with externalizing symptoms were moderated by warm and supportive parenting behaviors. Conversely, harsh parenting was linked to increased levels of externalizing symptoms, particularly in the context of low income. Conclusions: Findings suggest that the presence of multiple risk factors may incur greater vulnerability to externalizing problems, while warm and supportive parenting practices may provide a buffer against externalizing problems for adolescents exposed to physical abuse. Links between ACEs, SES, parenting, and youth adjustment should continue to be explored, highlighting parenting as a potentially important and malleable intervention target. Highlights: SES was associated with externalizing and internalizing symptoms. ACEs exposure and parenting were associated with externalizing symptoms. The presence of multiple risk factors corresponded to greater symptoms for youth. Parenting, a malleable treatment target, emerged as a moderator of effects.